Pengaruh Bauran Promosi Terhadap Keputusan Pembelian Teh Pucuk Harum di Kecamatan Tembalang - Damanik, Obedmeto Oswaldo (Universitas Galuh, 2025)
This study aims to analyze the promotional strategies carried out by PT Mayora Indah and analyze the factors that influence purchasing decisions for Teh Pucuk Harum products. The location of the study will be carried out in two sub – districts in Tembalang District including Tembalang and Sendangmulyo. The research location was carried out in two retail stores, Indomaret and Alfamart. The study used 100 respondents using a non-probability sampling method with a purposive sampling technique. Data analysis used descriptive analysis and multiple linear regression analysis. The results showed that advertising, personal selling, sales promotion, direct marketing, public relations, had a significant influence on purchasing decisions simultaneously. Personal selling, sales promotion and direct marketing had a very significant influence partially, while advertising and public relations did not have a significant effect partially.